Distribution of Heavy Metals and Macrobenthic Invertebrates in Sediment of the Escravos Estuary, Nigeria - Perekibina A Bariweni; Amarachi P Onyena; Michael E Okiotor; Abraham Ogheneruemu Ekperusi (International Journal of Maritime and Interdisciplinary Research, 2024)
This study evaluated the distribution of heavy metals and the macrobenthic invertebrates in sediments at an estuary impacted by wastewater effluents from petroleum and gas operations in the Niger Delta region of Nigeria. Sediment samples were collected monthly for six months from five locations by standard methods and analysed for pH, EC, TOC, nitrate, phosphate, sulphate, Cd, Pb, Zn, Cu, Fe, TPH and macrobenthic invertebrates. The distribution of heavy metals in sediments was in the order of Fe > Zn > Pb > Cu > Cd. Mean Cd (7.31±12.76) and TPH (66.81±32.64) were above the permissible limits of 0.8 mg/kg and 50.0 mg/kg respectively. A total of 65 individuals belonging to 7 species, 7 genera, 7 families and 3 phyla were recorded. Molluscs accounted for 60% of the macrobenthic invertebrates with decreased species diversity and dominance across the sampled sites. Geo-accumulation index and contamination factor showed moderate to high contamination for Cd and Pb, while ecological and pollution index reveal severe risk of ecological degradation due to increased metal contamination of the Escravos Estuary. This study highlights the impact of petrochemical operations on the ecology of the Escravos Estuary. There is a need for the regular monitoring of wastewater effluents from petroleum and gas operations into the estuary to prevent ecosystem collapse in the region.
Keywords: Heavy metals; Environmental monitoring; TPH; Benthic organisms; Physicochemical properties; Escravos estuary